The influence of Korean pop culture on purchasing behavior of Korean products among consumers in Klang Valley - Osman, Syuhaily; Ismail, Nur Farah Mardhiah (Human Resource Management Academic Research Society, 2022)
Malaysia is currently stricken with Korean fever in all local industries including fashion, food and cosmetic. K-dramas, K-music, and K-culture are building a stronghold in the country with the younger generation becoming more fascinated towards South Korea’s cultural images. The main purpose of this study is to determine the influence of Korean pop culture on purchasing behavior of Korean products among consumers in Klang Valley. There were total of 200 respondents participated in this study who were selected via simple random sampling method. The data were collected through a set of self-administered questionnaires and analyzed by using the Package Statistical for Social Science (SPSS). The results demonstrated by Pearson product moment correlation analysis had indicated that there were significant relationships between perception towards Korean foods (r = .249, p = .000), Korean fashions (r = .426, p = .000) and Korean cosmetics (r = .230, p = .001) with purchasing behavior of Korean products. In addition, perception towards Korean fashions reported to be the most influential predictor (? = .387 p ?0.001) as indicated by the multiple regression analysis. Results suggest that consumers take note of products originating from Korea and they are able to critically assess products from different dimensions.